The Development of Agarwood Leaves Extract Powder Into Chocolate Spread - Mohd Fairuz, Nurul Ain; A.Talip, Balkis (Enhanced Knowledge in Sciences and Technology, 2025)
This study developed a chocolate spread with agarwood leaves extract powder (ALEP) for its functional properties. The formulation was optimized using Design Expert software to balance physical and sensory characteristics. The process involved drying, grinding, and spray-drying the leaves, then blending with sugar, vegetable oil, and skim milk powder. Results showed that ALEP improved the spread's functional properties but reduced sweetness and introduced bitterness. However, other attributes were well accepted by consumers. The optimal formulation was 40.0% sugar, 36.8% vegetable oil, and 16.8% skim milk powder, though further refinement is needed to improve flavor and consumer appeal. This study demonstrates the potential of ALEP-enriched spreads in the functional food market with necessary sensory adjustments.